Intrastromal Fluconazole - Effectiveness in the Surgery of Stromal Abscess in a Horse - Krebs, Carlos Otávio Eggres; Girondi, Giulia Brambila; Farencena, Fernanda Iensen; Corrêa, Luís Felipe Dutra; Cassanego, Guilherme Rech; da Rosa, Carolina Cauduro; Flores, Fabiano da Silva; Pigatto, Anita Marchionatti (Acta Scientiae Veterinariae, 2022)
Background: Due to its ocular microflora, the equine species is predisposed to develop mycotic ulcers which, when not properly treated, can lead to the formation of a stromal abscess. A stromal abscess occurs through the introduction of microorganisms into the corneal stroma. During re-epithelialization, the foreign body is encapsulated, thus creating a barrier that protects bacteria or fungi from treatment with antimicrobial medication. This framework can end up resulting in blindness due to chronic iridocyclitis, putting the animal’s vision at risk. The current work aims to report a case of corrective surgery for stromal abscess in a mare with the administration of intraoperative intrastromal fluconazole, in order to corroborate the effectiveness of the technique. Case: A 9-year-old mare was evaluated, with the complaint that her right eye was closed and “yellowish” and that she had already been treated with intramuscular injectable anti-inflammatory drugs based on flunexin meglumine (Banamine® - 50 mg) for 15 days, referring to a possible ulcer in the right eye. Ophthalmic screening resulted in a negative direct reflex and no threat response in the right eye. Examination of the conjunctiva showed congestion and chemosis. Examination of the cornea of the right eye was negative for Fluorescein and Green Lissamine tests, and opacity and corneal neovascularization were noted. The final diagnosis was a corneal abscess of probable fungal origin secondary to a keratomycosis. After the consultation, complementary blood and biochemical tests were performed, which showed normal results for the species in question, and treatment was started with eye drops based on atropine 1% (Fagra® - 20 mL), ciprofloxacin antimicrobial eye drops (Ciprovet Colirio® - 5 mL), and antifungal eye drops based on ketoconazole 1% (manipulated), in addition to an intramuscular injectable anti-inflammatory based on flunexin meglumine (Banamine® - 50 mg - 1.1 mg/kg SID) and an intramuscular injectable analgesic based on sodium dipyrone (Febrax® - 0.5 g - 15 mL/animal SID) until the day of surgery, which was booked for 3 days later. The surgical intervention was then instituted by the technique of anterior lamellar keratectomy followed by intrastromal hydration with fluconazole and the forming of a bipedicled flap, in order to remove the necrotic tissue and antigenic stimulation factors, while the conjunctival flap aimed to improve blood supply and protect the injured area, thus favoring local healing. For better postoperative quality for the animal, continuation of the same treatment as prior to surgery was prescribed for a period of 15 days. The return of the animal for the removal of the flap was scheduled for 45 days after surgery, however, due to the COVID-19 pandemic, there was a delay of 135 days. When the animal returned the flap was still stable. A second surgery was instituted for the removal of the flap, during which it was possible to affirm that the cornea had recovered total integrity and partial transparency with only a leukoma in the previous location of the abscess. Discussion: The technique of anterior lamellar keratectomy together with the use of a conjunctiva flap for the treatment of stromal abscess in horses is a known technique that is used routinely, although some cases report the formation of a second infection in the same space. However, there are few reports on the use of intrastromal hydration with antifungal medication adjuvant to the surgical technique, which, as shown in this report, proved to be effective since even with the issue of a delay in removing the conjunctival flap, the eye remained whole and there was no second infection. The use of this technique can therefore be indicated for the treatment of stromal abscess in horses, given the safety that the application of intrastromal antifungal provides. Keywords: azole, abscess, stromal, keratectomy, ophthalmology, equine, mare. Descritores: azol, abscesso, estroma, ceratectomia, oftalmologia, equino, égua.